Zirconia-supported 12-tungstophosphoric acid as a solid catalyst for the synthesis of linear alkyl benzenes - Devassy, Biju M.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2005)
The liquid-phase alkylation of benzene with 1-octene and 1-dodecene was investigated with zirconia-supported 12-tungstophosphoric acid (TPA) as catalysts. We prepared the catalysts, with different TPA loading (5-20 wt% calcined at 750 degrees C) and calcination temperatures (15 wt% calcined from 650 to 850 degrees C), by suspending hydrous zirconia in a methanol solution of TPA, followed by drying and calcination. These catalysts were characterized by X-ray diffraction, DTG-DTA, FTIR pyridine adsorption, NH3-TPD, and P-31, MAS NMR spectroscopy measurements. The catalyst with optimum TPA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents and characterized by P-31 MAS NMR spectroscopy. The XRD results indicate that TPA stabilizes the tetragonal phase of zirconia. The catalysts show both Bronsted and Lewis acidity, and 15% TPA on zirconia calcined at 750 degrees C shows the highest acidity. P-31 MAS NMR spectra show two types of phosphorous species: one is the Keggin unit and the other is the decomposition product of TPA. The relative amount of each depends on TPA loading, calcination temperature, and the solvent used for the catalyst preparation. Under reaction conditions of 84 degrees C and a benzene/1-olefin molar ratio of 10 (time 1 h), the most active catalyst, 15% TPA, calcined at 750 degrees C, gave more than 98% olefin conversion with selectivity for 2-phenyl octane (53.5%) and 2-phenyl dodecane (47%). (c) 2004 Elsevier Inc. All rights reserved.
Keywords: 12-tungstophosphoric acid; linear alkyl benzene; solvent effect; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia